Triple Elimination Screening Examination Results for Pregnant Women of Healthy Reproductive Age in First Trimester at Lebdosari Community Health Center, Semarang City - Nissa Aullya; Fitriani Kahar (MultiTech Publisher, 2024)
Pregnant women are one of the populations at risk of contracting HIV infection, syphilis and Hepatitis B. The prevalence of HIV/AIDS transmission from mother to child is 20-50%, of which 5-10% occurs during pregnancy. Syphilis transmission is 69-80% and Hepatitis B transmission is more than 90% with the potential for transmission during pregnancy and childbirth being very high. Based on RI Minister of Health Regulation No. 52 of 2017 concerning the Elimination Program for Transmission of HIV, Syphilis and Hepatitis B from Mother to Child or often called